2001
DOI: 10.1080/00288330.2001.9516982
|View full text |Cite
|
Sign up to set email alerts
|

Factors regulating the downstream migration of mature eels (Anguillaspp.) at Aniwhenua Dam, Bay of Plenty, New Zealand

Abstract: The downstream migrations of mature longfinned eels (Anguilla dieffenbachii Gray, 1842) and shortfinned eels (Anguilla australis Richardson, 1848) were investigated at Aniwhenua Dam on the Rangitaiki River between 1992 and 1998. Migrants were mostly females over 1000 mm total length (TL) with otoliths indicating rapid growth rates. Migrations, which occurred on a few nights each autumn, generally began once water temperatures began to decline and ended when temperatures dropped below c. 11 °C. Rainfall and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
60
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 30 publications
11
60
0
Order By: Relevance
“…Targeting night periods for flow releases and excluding times when water temperatures are below 10°C would reduce potential generation losses, but unlike other catchments (e.g. Boubée et al, 2001;Watene & Boubée, 2005;Boubée & Williams, 2006), we found few occasions when migrations in Lake Manapouri were clearly triggered by rainfall (inflow) events, although eel activity did increase when lake levels rose. Additional data gathering (existing transponder batteries are due to expire around July 2006), including the tagging and tracking of silver eels from Lake Te Anau, is in progress to determine if other environmental factors, either singly or in combination (e.g.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Targeting night periods for flow releases and excluding times when water temperatures are below 10°C would reduce potential generation losses, but unlike other catchments (e.g. Boubée et al, 2001;Watene & Boubée, 2005;Boubée & Williams, 2006), we found few occasions when migrations in Lake Manapouri were clearly triggered by rainfall (inflow) events, although eel activity did increase when lake levels rose. Additional data gathering (existing transponder batteries are due to expire around July 2006), including the tagging and tracking of silver eels from Lake Te Anau, is in progress to determine if other environmental factors, either singly or in combination (e.g.…”
Section: Discussionmentioning
confidence: 56%
“…After several decades in fresh water (up to 60 years for shortfins and 100 years for longfins), eels mature and migrate downstream to spawn at sea. This downstream migration mainly occurs in autumn (Cairns, 1941;Hobbs, 1947;Todd, 1981a;Boubée et al, 2001), but some migrations have been recorded in spring and summer (Burnet, 1969;Todd, 1981a;Boubée et al, 2001;Watene et al, 2003). Although a small estuarine and marine fishery exists for shortfins, longfins have only occasionally been recorded at sea.…”
Section: Introductionmentioning
confidence: 94%
“…Allowing downstream migration to occur is essential for protecting diadromous species (e.g. eels, lamprey, whitebait species) that go to sea to complete their life cycle because this is the brood stock that will be maintaining the future fishery (Boube´e et al 2001). In Ireland, McCarthy et al (2008) showed that escapement rates for seaward migrating eels could be significantly increased by trapping eels above dams and transporting them downstream.…”
Section: Discussionmentioning
confidence: 97%
“…Rather, it appears that the proximate cues for migration of barramundi from freshwater are complex (McDowall 1988) or are linked to rare climatic events. Rainfall, temperature, moon phase, olfaction and fish condition have all been identified as important cues for migration of many freshwater and marine fishes (McDowall 1988, Naslund et al 1993, Boubee et al 2001, Hodgson & Quinn 2002, Okamura et al 2002. Similar cues are probably involved in barramundi migration.…”
Section: Discussionmentioning
confidence: 99%